THE EFFECT OF SEFT THERAPY ON THE LEVEL OF DYSMENORAL PAIN IN UMP STUDENTS - Hardiyani, Tati; Utami, Hernastiti Sedya; Grafiyana, Gisella Arnis (Jambura Nursing Journal, 2025)
Dysmenorrhoea is a painful disorder that most women experience every month. The impact that occurs if dysmenorrhea is left untreated or not treated properly is that it can cause disruption of daily activities, infertility, undetected pregnancy, ectopic cyst rupture, uterine perforation from the IUD and infection. Based on these impacts, dysmenorrhea must be treated immediately, so that these impacts do not interfere with daily activities or activities as well as a person's psychological condition. One non-pharmacological technique to reduce dysmenorrhea is SEFT therapy. Spiritual Emotional Freedom Technique (SEFT) is a complementary therapy in the Mind-Body Therapy category, which can be used to treat physical problems including dysmenorrhea pain. Based on the description above, researchers are interested in researching "The Effect of SEFT Therapy on Dysmenorrhoea Pain Levels in UMP Students". The purpose of this study was to determine the effect of SEFT therapy on the level of dysmenorrhoea pain in UMP students. The research design used a Quasi Experimental pre-test and post-test design without control group design. The sampling technique uses non-random sampling with total sampling. Data analysis used paired t-test. The results of the characteristics respondents showed that the average age of respondents is 20 years and the average duration of menstruation is 6 days with the shortest period being 3 days and the longest period being 9 days. The average dysmenorrhea pain level before therapy was 5.8 and the average dysmenorrhea pain level after therapy was 2.6. There is a difference in the level of dysmenorrhea pain before and after SEFT therapy with a p-value of 0.001. Conclusion: Providing SEFT therapy influences the level of dysmenorrhoea pain in UMP students.